2003
DOI: 10.1080/0020754031000152550
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of vibratory bowl finishing

Abstract: Although vibratory finishing has been in commercial use for over 40 years, relatively little fundamental information is known about the process, and industrial practice remains largely based on empiricism and trial and error. An experimental investigation into the vibratory bowl finishing process was conducted using material removal rate and surface roughness as the dependent variables. Bowl performance can best be described in terms of acceleration and depends primarily on the feed weights used, while bowl lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 3 publications
2
35
0
Order By: Relevance
“…(5) For the first time in vibratory finishing, the equivalent chip thickness h eq and the specific energy u were estimated based on the proposed model. (6) The estimated h eq is (10 À7 -10 À6 ) of typical values in grinding. (7) The estimated u is 200-1200 J/mm 3 which is 10-100 times higher than typical values in grinding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) For the first time in vibratory finishing, the equivalent chip thickness h eq and the specific energy u were estimated based on the proposed model. (6) The estimated h eq is (10 À7 -10 À6 ) of typical values in grinding. (7) The estimated u is 200-1200 J/mm 3 which is 10-100 times higher than typical values in grinding.…”
Section: Discussionmentioning
confidence: 99%
“…Also, very small sliding motion of media on workpieces was indicated. Domblesky et al [6,7] investigated bowl type vibratory finishing processes and proposed a model to describe material removal rate. The model indicated that the rate remained constant over time and was governed by bowl acceleration, workpiece mass and velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Domblesky et al [14,15] conducted an experimental investigation of the vibratory finishing process, and presented the model of material removal rate as a function of bowl acceleration. Fraas [16] provided useful results in the motion analysis of granular solids in fluidized beds.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be noted that, for the range of materials used in the study, increasing the diameter of the abrasive grain increases the volume that is removed from the workpiece. Domblesk and Dennis [13,14] suggested that the particle shape is not the only variable that controls the behaviour of manufactured abrasives. The relationship between particle shape and packing behaviour needs to be understood before the former can be used to accurately predict the wear-rate.…”
Section: Media Capabilitymentioning
confidence: 99%